Proving the Dual Electronic Structure of Charged Metal-Molecule Interfaces: Surface-Enhanced Raman Scattering of Cyanide Adsorbed on a Nanostructured Silver Electrode - Valdivia Mantas, Samuel; Aranda, Daniel; Ávila-Ferrer, Francisco José; Soto-Martín, Juan; López-Tocón, Isabel; Otero-Fernández-de-Molina, Juan Carlos (ACS Publications, 2020)
Experimental and theoretical calculations confirm, for the first time, the existence of two different kinds of electronic structures of a surface complex formed by a particular molecule bonded to charged metal electrodes, clusters, or nanoparticles. Surface-enhanced Raman scattering (SERS) of cyanine adsorbed on a silver electrode shows three regions, which are selected by the electrode potential and characterized by the differentiated response of the vibrational wavenumbers of the ν(CN) stretching band to the electrode potential. The combination between the experimental SERS and DFT calculations has allowed for relating the three regions to chemisorbed (C-hybrid) and physisorbed (P-hybrid) surface complexes, where cyanide is bonded through the carbon on top of a single silver atom of the surface and to bidentate species, respectively. The electrode potential selects one or another type of electronic structure of the surface complex, which are of different natures and with a differentiated response to the applied potential. The electric potential tunes smoothly the wavenumbers, bond energies, and injected charges of the P-hybrid at more negative potentials than that of the zero charge of the electrode, but the very strong C-hybrid prevents significant changes of these properties at positive excesses of charge. The existence of the dual electronic structure of metal-molecule interfaces might require reinterpreting experiments that are usually discussed by resorting to, for instance, the reorientation of the adsorbate, the formation of complexes with different stoichiometries, the existence of nonequivalent local sites on the surface, or to instrumental artifacts.
Keywords: Efecto Raman; Anions; Electrodes; Inorganic Carbon Compounds; Quantum Mechanics; Silver